Pope's Day and the Language of Popery in Eighteenth‐Century New England. (16th January 2022) - Ritter, Luke
Abstract : This article explains how American colonists' commemoration of religious conflicts in the past, particularly the Gunpowder Plot of 1605, gradually diverged from British systems of discourse. In the Revolutionary Era, Americans commemorated Guy Fawkes Day, a holiday which had initially been established by the king of England to solidify English nationalism, so as to criticise and overthrow British governance. The perseverance of Guy Fawkes Day, or "Pope's Day, " in eighteenth‐century New England, where Puritan authorities declared the holiday illegal, testified to its anti‐authoritarian as well as anti‐Catholic appeal among common people. The apocalyptic pitch of anti‐Catholicism reached a new height in colonial America during the so‐called First Great Awakening of the 1740s as conflicts with the French and Indians escalated. During the 1760s, the Pope's Day constituency of Boston, initially bent on liberating themselves from official interference at the local level, turned their animus against recent British policies, such as the Stamp Act of 1765, and eventually transformed themselves into revolutionary crowds, chanting, "No King, No Popery!" In the early United States, anti‐Catholic sentiment no longer promoted English nationalism, but it remained a powerful source of American identity and a potent motivation for rebellion against local authorities.